Body image and condomless anal sex among Young Latino sexual minority men - Brady, John P. (Behav Res Ther, 2018)
OBJECTIVE: To investigate body image and condomless anal sex (CAS) among young Latino sexual minority men (SMM)—a population with health disparities in HIV and body image concerns. METHODS: Participants were 151 young Latino SMM from the San Diego area who were HIV-negative or un-known. Participants completed a questionnaire online in either English or Spanish, which included body image and sexual behavior items. A binary CAS variable was created based on the number of CAS partners reported (0 vs 1 + over past 3 months). A logistic regression was conducted with body dissatisfaction, appearance investment, and their interaction term entered as predictor variables and CAS as the outcome. RESULTS: Of 151 participants, 54 (35.8%) reported no CAS in the past 3 months. Appearance investment, but not body dissatisfaction, was associated with higher odds of CAS. However, a significant interaction indicated that body dissatisfaction was associated with higher odds of CAS when appearance investment was high. CONCLUSIONS: Young Latino SMM who are highly invested in, and dissatisfied with, their appearance may be at significantly increased risk for acquiring HIV through elevated odds of CAS. Reducing appearance concerns in this population may lead to reductions in HIV risk behaviors.